Women in Pentecostal and Charismatic ministry : informing a dialogue on gender, church, and ministry - English de Alminana, Margaret. (Global Pentecostal and Charismatic Studies, 2016)
Women in Pentecostal and Charismatic Ministry: Informing a Dialogue on Gender, Church, and Ministry , co-edited by Margaret English de Alminana and Lois E. Olena, concerns women and Pentecostalism. It introduces the way the Pentecostal/charismatic movement has been shaped by and has shaped women from its beginning and offers a wide variety of responses to the opportunities and limitations women have experienced in their commitment to religious service. Scholars, activists, leaders, and exemplars from a variety of disciplines reflect on the question: How have women responded to a religious context that has depended upon their gifts while, at the same time, limited their voices and perspectives? This volume offers missing and/or silent voices an important corrective and a way forward to shape gender-focused discussions. Contributors are: Estrelda Yvonne Alexander, Peter Althouse, Linda M. Ambrose, Melissa L. Archer, Amy C. Artman, Denise A. Austin, Kate Bowler, Barbara Cavaness-Parks, Loralie Robinson Crabtree, Naomi Dowdy, Margaret English de Alminana, Beth (A. Elizabeth) Grant, Jacqueline Grey, Mimi R. Haddad, Jennifer A. Miskov, Stephanie L. Nance, Lois E. Olena, Ava Kate Oleson, Joy E. A. Qualls, and Zachary Michael Tackett.